2014
DOI: 10.1371/journal.pone.0084733
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology of Spinal Cord Injuries and Risk Factors for Complete Injuries in Guangdong, China: A Retrospective Study

Abstract: BackgroundSpinal cord injuries are highly disabling and deadly injuries. Currently, few studies focus on non-traumatic spinal cord injuries, and there is little information regarding the risk factors for complete injuries. This study aims to describe the demographics and the injury characteristics for both traumatic and non-traumatic spinal cord injuries and to explore the risk factors for complete spinal cord injuries.MethodsA retrospective study was performed by reviewing the medical records of 3,832 patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

7
66
0
8

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(81 citation statements)
references
References 30 publications
7
66
0
8
Order By: Relevance
“…Simple decompression (88 patients in our study) was used in TSCI patients without fracture of spine, and TSCI patients who encountered severe spine fracture were treated with decompression and internal fixation (116 patients). Yang et al 15 reported the similar conditions of treatment options in Guangdong. To our knowledge, a few studies reported treatment options.…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…Simple decompression (88 patients in our study) was used in TSCI patients without fracture of spine, and TSCI patients who encountered severe spine fracture were treated with decompression and internal fixation (116 patients). Yang et al 15 reported the similar conditions of treatment options in Guangdong. To our knowledge, a few studies reported treatment options.…”
Section: Discussionmentioning
confidence: 86%
“…It is generally known that TSCI exerts a substantial financial burden on patients and society on account of the tremendous cost of health-care treatments, decreased quality of life and social participation, as well as lost productivity. 15 Consequently, the research of epidemiological profile can support the effective use of medical resources and the implementation of preventive measures. To our knowledge, such epidemiology research of TSCI from developing countries is comparatively less in comparison with developed countries, mainly because of the lack of National SCI Register System.…”
Section: Discussionmentioning
confidence: 99%
“…Although throughout the paper it has been emphasized that gender-specific analysis of the data from all centers has been performed, nevertheless the male/female ratio for the 2 NGOs has not been provided despite their claim, to have these data. The low male/female ratio has been previously reported in SCI populations only in the fifth and sixth decades of their life [6] , but the mean age of SCI patients in Iran has been reported to be about 38.2 years [2] , although the standard deviation for age in this study has not been provided, the mean age is far from this age range.We conclude that the male/female ratio has been underestimated in this report. The previously reported epidemiological studies from Iran are not concordant with findings of the paper.…”
mentioning
confidence: 67%
“…1 Each year, 12 000 to 20 000 people sustain SCI in North America, and almost 2.5 million people worldwide live with SCI, experiencing immense personal, psychosocial, social, and financial burden. 27 Nearly half of the victims of SCI suffer a complete deficit, and one-third remain tetraplegic for life. While little can be done currently to undo or repair the primary injury to the spinal cord, great hope lies in interrupting the molecular cascades triggered by primary injury that are believed to worsen outcome.…”
mentioning
confidence: 99%